2015
DOI: 10.6018/eglobal.14.1.196021
|View full text |Cite
|
Sign up to set email alerts
|

Políticas públicas en la promoción de la salud del adolescente en la escuela: concepción de los gestores

Abstract: Nº 37 Enero 2015Página 250 ADMINISTRACIÓN -GESTIÓN -CALIDADPolíticas públicas en la promoción de la salud del adolescente en la escuela: concepción de los gestores RESUMENEl estudio tuvo como objetivo conocer las políticas públicas de promoción de la salud del adolescente en la escuela propuestas y desarrolladas bajo la responsabilidad de los gestores de educación y salud en el municipio de Recife-PE.Investigación cualitativa del tipo exploratoria-descriptiva. Participaron de la investigación 26 sujetos, entr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
3
0
2
Order By: Relevance
“…Pesquisa realizada com gestores avaliou o PSE como a única política para assistência integral do escolar, pelo estabelecimento de ações intersetoriais para o atendimento aos adolescentes no âmbito escolar 46 , com potencial capacidade de interferir positivamente na vida desses estudantes 29 , reorientar para a integralidade em saúde 37 , com ações direcionadas às suas realidades 26 . Ademais, segundo Barbieri e Noma 34 , apresentou-se como importante iniciativa no âmbito da luta democrática por direitos.…”
Section: Análise Dos Fatores Internos Ao Pse Grupo Fortalezasunclassified
See 1 more Smart Citation
“…Pesquisa realizada com gestores avaliou o PSE como a única política para assistência integral do escolar, pelo estabelecimento de ações intersetoriais para o atendimento aos adolescentes no âmbito escolar 46 , com potencial capacidade de interferir positivamente na vida desses estudantes 29 , reorientar para a integralidade em saúde 37 , com ações direcionadas às suas realidades 26 . Ademais, segundo Barbieri e Noma 34 , apresentou-se como importante iniciativa no âmbito da luta democrática por direitos.…”
Section: Análise Dos Fatores Internos Ao Pse Grupo Fortalezasunclassified
“…A identificação de fragilidades contidas no programa é tarefa essencial para que ele seja ajustado em direção a uma maior eficiência. Os estudos mostraram expressiva presença desses fatores, nos quais a desarticulação entre os setores saúde e educação se apresenta com maior relevância, cujas ações comprometem a intersetorialidade e a integralidade, ainda insuficientes 18,25-33,35,42,43, 46 . Identificou-se a falta de protocolos para o desenvolvimento das ações intersetoriais, cujas agendas setoriais já são previamente elaboradas 35 , havendo desconexão e distanciamento entre os serviços 26,38,40, 43 .…”
Section: Grupo Fragilidadesunclassified
“…A research carried out with managers evaluated the PSE as the only policy for comprehensive care for students, through the establishment of intersectoral actions for the care of adolescents in the school environment 46 , with the potential capacity to positively interfere in the lives of these students 29 , redirecting them towards integrality in health 37 , with actions directed to their realities 26 . Furthermore, according to Barbieri and Noma 34 , it was presented as an important initiative within the scope of the democratic struggle for rights.…”
Section: Analysis Of Factors Internal To the Pse Strengths Groupmentioning
confidence: 99%
“…The identification of weaknesses contained in the program is an essential task for it to be adjusted towards greater efficiency. Studies have shown an expressive presence of these factors -in which the disarticulation between the health and education sectors is the most relevant -which actions compromise intersectoriality and integrality, still insufficient 18,25-33,35,42,43, 46 . The lack of protocols for the development of intersectoral actions was identified, which sectoral agendas are prepared in advance 35 , with disconnection and distance between services 26,38,40, 43 .…”
Section: Weakness Groupmentioning
confidence: 99%
See 1 more Smart Citation